Ensaios empíricos sob a análise de identificação parcial e sensibilidade na educação brasileira - Costa, Leandro Oliveira (2010)
This thesis brings two empirical studies using the methodologies of Sensitivity Analysis and Partial Identification on the causality of interventions of relevant importance to Brazilian education. These analyses are important tools, few times or never used in Brazilian literature, to investigate the questionable veracity of the assumptions used in the widespread Propensity Score Matching methodology. The first chapter expands the research on the performance gap between students from public and private schools with an analysis of Partial Identification. Proposed initially at Manski (1989), this methodology allows to question the assumptions commonly used in statistical and econometric models that points the private school system as more efficient. The second chapter investigates the effect of teacher’s stability on teaching quality. The goal is contributes to the Brazilian research on the characteristics of the teacher that affect student performance, inserting a nonmonetary factor related to hiring qualified professionals. Additionally, the estimative robustness will be verified by the Sensitivity Analysis proposed by Rosenbaum and Rubin (1983). The results indicate an overestimation of the positive effect of private school in studies of the Brazilian educational system and the significant impact of the stability condition of teachers on the quality of teaching in public schools.